Property of mixing of continuous classical systems with strong superstable interactions - Rebenko, A. L.; Tertychnyi, M. V. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
We consider an infinite system of point particles in R^d, interacting via a strong superstable two-body potential φ of finite range with radius R. In the language of correlation functions, we obtain a simple proof of decrease in correlations between two clusters (two groups of variables) the distance between which is larger than the radius of interaction. The established result is true for sufficiently small values of activity of the particles.